A hydroxyl acrylic resin, a method for preparing the same, a paint and a coating

CN119306875BActive Publication Date: 2026-10-27TIANJIN BEACON PAINTING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411495517.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2026-10-27
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

然而当前市场上常见的高固体含量羟基丙烯酸树脂的粘度通常较高,为保证涂料体系粘度适合能够正常施工,在实际使用中又要额外加入有机溶剂稀释剂,这会导致VOC排放进一步提升而且增大了涂料整体的成本

Benefits of technology

[0040]1)通过调整配方中含甲基侧链的丙烯酸酯类单体与含苯环结构硬单体的不同组合,其中含甲基侧链的丙烯酸酯类单体由于侧链存在亲油性的甲基,其极大的提高了后续涂料配方的分散性能,由于此类结构下的双键不易旋转因此性质会比丙烯酸酯类更加稳定。同时引入空间位阻较大的刚性苯环结构不但能够弱化分子链间作用力,使聚合物粘度降低,还赋予了丙烯酸树脂的硬度、干性、耐腐蚀性能等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A kind of hydroxyl acrylic resin and its preparation method, paint and coating.The raw material of the hydroxyl acrylic resin, by mass percentage, consists of 4-15% methyl methacrylate, 3-12% butyl methacrylate, 15-25% butyl acrylate, 8-15% hydroxyethyl acrylate, 15-25% styrene, 0.3-1.0% acrylic acid, 0.1-2.5% initiator, 21-40% organic solvent.By adjusting the ratio of acrylic ester monomer containing methyl side chain and hard monomer containing benzene ring structure, the viscosity of the prepared hydroxyl acrylic resin is controlled within 1500-3000 mPa·s, and the solid content of the paint can reach about 70%.Through continuous screening and optimization of process, the monomer conversion rate of acrylic resin can reach more than 99%, and the hydroxyl acrylic resin has excellent adhesion, higher hardness and acid and alkali resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This article relates to the field of acrylic resins, and more particularly to a high-solids, low-viscosity hydroxyl acrylic resin for steel structure anti-corrosion coatings, its preparation method, as well as coatings including the resin and coatings formed by the coatings. Background Technology

[0002] In recent years, with increasingly stringent environmental protection requirements, the international market has imposed stricter restrictions on VOC emissions from coatings. Currently, low-pollution organic solvent coatings mainly include water-based coatings, powder coatings, radiation-cured coatings, and high-solids coatings. High-solids, low-viscosity hydroxyl acrylic resins, as a new type of high-solids coating binder, have attracted considerable attention in recent years. High-solids resins have lower organic solvent content, which can reduce VOC emissions, and they also possess excellent water resistance, chemical corrosion resistance, good adhesion, and superior optical transparency. They are suitable for various coating applications, such as automotive coatings, architectural coatings, and electronic product surface coatings. However, the viscosity of commonly available high-solids hydroxyl acrylic resins is usually high. To ensure suitable viscosity for normal application, additional organic solvent diluents must be added in actual use, which further increases VOC emissions and the overall cost of the coating. This significantly limits their application in steel structure anti-corrosion coatings. Therefore, it is necessary to invent and design a hydroxyl acrylic resin that combines high solids content with low viscosity to solve these problems. Summary of the Invention

[0003] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of the claims.

[0004] Based on the problems raised in the background technology, this application provides a hydroxyacrylic resin with high solids content and low viscosity, as well as a preparation process, by adjusting different combinations of acrylate monomers containing methyl side chains and hard monomers containing benzene ring structures. In terms of the preparation process, by continuously adding a specific initiator and continuing the reaction at a selected temperature, the monomer conversion rate of the resin can reach 99%. Preferably, the prepared hydroxyacrylic resin varnish has a solids content of about 70%, and the viscosity of the resin is controlled within 1500-3000 mPa·s. It exhibits high hardness and adhesion, as well as excellent weather resistance and acid and alkali resistance.

[0005] To achieve the above objectives, the following technical solution is adopted in this application:

[0006] The first aspect of this application provides a hydroxyl acrylic resin, the raw materials of which include: (meth)acrylate monomer, acrylic acid, initiator and organic solvent, and aromatic vinyl monomer.

[0007] In one exemplary embodiment, the hydroxy acrylic resin has a monomer conversion rate of 99%, a solid content of 66.6%-66.8%, and a viscosity controlled at 1500-3000 mPa·s.

[0008] In one exemplary embodiment, the (meth)acrylate monomer is one or a mixture of several of methyl methacrylate, butyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methyl acrylate, and propyl acrylate.

[0009] Preferably, the (meth)acrylate monomer is one or a mixture of several of methyl methacrylate, butyl methacrylate, butyl acrylate, and hydroxyethyl acrylate.

[0010] In one exemplary embodiment, the aromatic vinyl monomer is styrene.

[0011] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, include: 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, and 21%-45% organic solvent.

[0012] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, consist of the following: 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, and 21%-45% organic solvent.

[0013] In one exemplary embodiment, the organic solvent is one or a mixture of xylene, toluene, butyl acetate, ethyl acetate, butanone, and pentanone;

[0014] Preferably, the organic solvent is a mixture of xylene and butyl acetate.

[0015] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, include: 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, 20%-30% xylene, and 1%-15% butyl acetate.

[0016] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, consist of the following: 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, 20%-30% xylene, and 1%-15% butyl acetate.

[0017] In one exemplary embodiment, the mass ratio of methyl-side-chain acrylic monomers (methyl methacrylate, butyl methacrylate) to benzene ring-structured hard monomers (styrene) in the hydroxyl acrylic resin is 1:1.4-2.8.

[0018] In one exemplary embodiment, the initiator is one of azobisisobutyronitrile, azobisisoheptane, benzoyl peroxide, cumene hydroperoxide, potassium persulfate, and ammonium persulfate. The initiator has a half-life of 8-12 hours at 70°C; the higher the temperature, the shorter the half-life of the initiator, resulting in more free radical active sites generated during decomposition and a relatively lower viscosity of the resulting resin.

[0019] In one exemplary embodiment, the initiator is benzoyl peroxide.

[0020] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, consist of the following: 6.2% methyl methacrylate, 5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 21.3% styrene, 0.8% acrylic acid, 2.5% initiator, 21.8% xylene, and 11% butyl acetate;

[0021] In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:1.9.

[0022] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, consist of the following: 5.4% methyl methacrylate, 4.5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 22.7% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate;

[0023] In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:2.3.

[0024] In one exemplary embodiment, the raw materials of the hydroxyacrylic resin, by mass percentage, consist of the following: 4.8% methyl methacrylate, 4% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 23.8% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0025] In the hydroxy acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:2.7.

[0026] The second aspect of this application provides a method for preparing the above-mentioned hydroxyl acrylic resin, comprising the following steps:

[0027] 1) According to the formula, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and part of the initiator are drawn into a dropping container and stirred until a mixture is obtained;

[0028] 2) Add a portion of xylene and the total amount of butyl acetate to the reactor as a base and heat it. Then, drop the mixture from the dropper into the reactor. After the addition is complete, continue copolymerization.

[0029] 3) Add the remaining xylene and initiator, keep warm, then cool down and discharge the material.

[0030] In an exemplary embodiment, step 1) includes: according to the ratio, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, and acrylic acid are drawn into a dropping tank, a portion of the initiator is weighed and added into the dropping tank, and stirring is started until the mixture is uniformly dissolved to obtain the mixture;

[0031] Optionally, the amount of initiator added is 80%.

[0032] In one exemplary embodiment, step 2) includes: adding 80% of xylene and all of butyl acetate to a reaction vessel as a base and heating it; dripping the mixture from the dropper into the reaction vessel; and maintaining copolymerization for 1 hour after the dripping is complete.

[0033] Optionally, 80% of xylene and all of butyl acetate are added to the reaction vessel as a base, and the temperature is raised to 124±2℃ and maintained for 10 minutes within 1.5 hours;

[0034] Optionally, the mixture in the dropping vessel is added dropwise into the reaction vessel over 2-2.5 hours at 124±2℃ without reflux, and copolymerization is maintained for 1 hour after the addition is complete.

[0035] In an exemplary embodiment, step 3) includes: adding the remaining xylene and initiator mixture dropwise into the reactor over 5-10 minutes at 124±2°C, maintaining copolymerization for 2 hours, and then cooling the reactor to 80°C to discharge the hydroxyl acrylic resin.

[0036] A third aspect of this application provides a hydroxy acrylic resin prepared by the above-described method for preparing hydroxy acrylic resin.

[0037] The fourth aspect of this application provides a coating material comprising the aforementioned hydroxyl acrylic resin.

[0038] The fifth aspect of this application provides a coating formed from the above-described coating material.

[0039] Compared with the prior art, this application has the following beneficial effects:

[0040] 1) By adjusting the different combinations of acrylate monomers with methyl side chains and hard monomers with benzene ring structures in the formulation, the acrylate monomers with methyl side chains, due to the presence of lipophilic methyl groups in the side chains, greatly improve the dispersion performance of subsequent coating formulations. Because the double bonds in this structure are not easily rotated, their properties are more stable than those of acrylate monomers. Simultaneously, the introduction of rigid benzene ring structures with greater steric hindrance not only weakens the intermolecular forces, reducing polymer viscosity, but also imparts to acrylic resins properties such as hardness, drying properties, and corrosion resistance.

[0041] 2) The existing preparation process is improved by adopting a continuous reaction and initiator replenishment method. During the reaction, the temperature is controlled by heating with medium-temperature heat transfer oil and cooling with cold oil. The monomer conversion rate of the final hydroxyl acrylic resin can reach 99%, and the varnish solid content of the resin is approximately 70%, with the resin viscosity controlled between 1500-3000 mPa·s. The hydroxyl acrylic resin prepared in this application has excellent workability and construction performance, and the steel structure anti-corrosion coating prepared accordingly exhibits excellent adhesion, high hardness, and acid and alkali resistance.

[0042] Other features and advantages of this application will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the application. Other advantages of this application may be realized and obtained by means of the methods described in the description. Detailed Implementation

[0043] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application will be described in detail below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.

[0044] The present invention will be further described in detail below with reference to specific embodiments, but these embodiments should not be construed as limiting the present invention. All raw materials used in this application are conventional products available on the market.

[0045] Example 1

[0046] A hydroxy acrylic resin is made from the following raw materials in weight percentages: 6.2% methyl methacrylate, 5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 21.3% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0047] In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:1.9.

[0048] The preparation method of the hydroxyl acrylic resin includes the following steps:

[0049] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator benzoyl peroxide were drawn into a dropwise addition vessel and stirred until a mixture was obtained.

[0050] Add 80% xylene and all of butyl acetate to the reaction vessel, heat to 124±2℃, and add the mixture in the dropping tank dropwise over 2-2.5 hours, maintaining copolymerization for 1 hour;

[0051] After the reaction is complete, add the remaining xylene and benzoyl peroxide, continue the reaction at a constant temperature for 2 hours, then cool down and discharge the material.

[0052] The obtained hydroxyl acrylic resin had a solid content of 66.8%, a theoretical solid content of 67%, a conversion rate of 99%, and a viscosity of 2317 mPa·s.

[0053] Example 2

[0054] A hydroxy acrylic resin is made from the following raw materials in weight percentages: 5.4% methyl methacrylate, 4.5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 22.7% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0055] In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:2.3.

[0056] The preparation method of the hydroxyl acrylic resin includes the following steps:

[0057] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator benzoyl peroxide were drawn into a dropwise addition vessel and stirred until a mixture was obtained.

[0058] Add 80% xylene and all butyl acetate to the reaction vessel, heat to 124±2℃, and add the mixture in the dropping tank dropwise over 2-2.5 hours, maintaining copolymerization for 1 hour;

[0059] After the reaction is complete, add the remaining xylene and benzoyl peroxide, continue the reaction at a constant temperature for 2 hours, then cool down and discharge the material.

[0060] The obtained hydroxyl acrylic resin had a solid content of 66.7%, a theoretical solid content of 67%, a conversion rate of 99%, and a viscosity of 2074 mPa·s.

[0061] Example 3

[0062] A hydroxy acrylic resin is made from the following raw materials in weight percentages: 4.8% methyl methacrylate, 4% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 23.8% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0063] In the hydroxy acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:2.7.

[0064] The preparation method of the hydroxyl acrylic resin includes the following steps:

[0065] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator benzoyl peroxide were drawn into a dropwise addition vessel and stirred until a mixture was obtained.

[0066] Add 80% xylene and all butyl acetate to the reaction vessel, heat to 124±2℃, and add the mixture in the dropping tank dropwise over 2-2.5 hours, maintaining copolymerization for 1 hour;

[0067] After the reaction is complete, add the remaining xylene and benzoyl peroxide, continue the reaction at a constant temperature for 2 hours, then cool down and discharge the material.

[0068] The obtained hydroxyl acrylic resin had a solid content of 66.6%, a theoretical solid content of 67%, a conversion rate of 99%, and a viscosity of 1766 mPa·s.

[0069] Comparative Example 1

[0070] A hydroxy acrylic resin is made from the following raw materials in weight percentages: 10.4% methyl methacrylate, 8.7% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 13.4% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0071] In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:0.7.

[0072] The preparation method is the same as in Example 1.

[0073] The obtained hydroxyl acrylic resin had a solid content of 66.6%, a theoretical solid content of 67%, a conversion rate of 99%, and a viscosity of 3714 mPa·s.

[0074] Comparative Example 2

[0075] A hydroxy acrylic resin is made from the following raw materials in weight percentages: 3.1% methyl methacrylate, 2.5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 26.9% styrene, 0.8% acrylic acid, 2.5% benzoyl peroxide, 21.8% xylene, and 11% butyl acetate.

[0076] In the hydroxy acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-structured hard monomers is 1:4.8.

[0077] The preparation method is the same as in Example 1.

[0078] The obtained hydroxyl acrylic resin had a solid content of 66.8%, a theoretical solid content of 67%, a conversion rate of 99%, and a viscosity of 1324 mPa·s.

[0079] Comparative Example 3

[0080] Compared with Example 1, Comparative Example 3 did not involve the preparation of acrylic resin. Instead, it was tested using a high-solids, low-viscosity hydroxyl acrylic resin available in Jiangsu Sanmu Market, and was labeled as Comparative Example 3.

[0081] Its solid content was found to be 65%, and its viscosity was 5304 mPa·s.

[0082] test:

[0083] The hydroxyl acrylic resins prepared in Examples 1-3 and Comparative Examples 1-3 were tested for their solid content, viscosity, acid value, and other performance indicators. The solid content of the resins was tested according to GB / T1725-2007 "Determination of Non-volatile Matter Content in Paints, Varnishes and Plastics"; viscosity was tested according to GB / T 2404-2008 "Method for Determination of Viscosity of Acrylic Resins"; acid value was tested according to GB / T12008.5—2010 "Determination of Acid Value of Polyether Polyols in Plastics"; fineness was tested according to GB / T 1724-1979 "Determination of Fineness of Coatings"; and color number was tested according to GB / T1722-92 "Determination of Color of Varnishes, Oils and Thinners". The test results are shown in Table 1.

[0084] Table 1 Performance indicators of high-solids, low-viscosity hydroxyl acrylic resins in the examples and comparative examples.

[0085]

[0086] Application Examples

[0087] 1. Take the hydroxyl acrylic resins obtained from Examples 1-3 and Comparative Examples 1-3 above and prepare them into varnishes according to the formulations in Table 2.

[0088] The surface drying time of the varnish was tested according to GB / T 1728-1979 "Determination of Drying Time of Paint Film and Putty Film", the flexibility was tested according to GB / T 1731-1993 "Determination of Flexibility of Paint Film", and the hardness was tested according to GB / T The hardness of paint films is tested according to GB / T 6739-2006 "Determination of Hardness of Paint Films by Pencil Method for Paints and Varnishes", adhesion is tested according to GB / T 9286-1998 "Cross-cut Test of Paint Films for Paints and Varnishes", impact resistance is tested according to GB / T 1732-1993 "Determination of Impact Resistance of Paint Films", gloss is tested according to GB / T 9754-2007, artificial aging resistance is tested according to GB / T 1865-1997 "Artificial Weathering and Artificial Radiation Exposure of Paints and Varnishes" and GB / T 1766-1995 "Rating Method for Aging of Paint and Varnish Coatings", and acid resistance, alkali resistance and salt spray resistance are tested according to the relevant testing standards in HG / T 2454—2014 "Soluble-based Polyurethane Coatings (Two-component)".

[0089] Table 2 Formulas for Acrylic Resin Industrial Varnishes

[0090] Hydroxyacrylate resins of Examples 1-3 or Comparative Examples 1-3 79.9% N-75 curing agent 19.9% Defoamer BYK-052n 0.1% Dispersant Afcona-5065 0.1%

[0091] 2. Paint film inspection

[0092] The prepared varnish was sprayed onto the surface of the polished tinplate, with a film thickness of 23±3μm. After drying, the performance was tested, and the results are shown in Table 3 below.

[0093] Table 3 Performance of hydroxyl acrylic resin coating

[0094]

[0095]

[0096] The above experimental results show that:

[0097] By adjusting different combinations of acrylic monomers with methyl side chains and hard monomers with benzene ring structures, particularly the ratio of methyl methacrylate, butyl methacrylate, and styrene, the results showed that as the styrene content increased, the overall viscosity, stain resistance, and water resistance of the resin improved due to the larger steric hindrance of the benzene ring. However, after exceeding a certain ratio, the resin became too rigid, and the paint film became brittle. Simultaneously, due to the presence of methyl side chains, the Tg of acrylic monomers with different chain lengths increased significantly, which to some extent neutralized the surface drying time and flexibility of the paint film. By coordinating the ratios of the two types of monomers, the hydroxyl acrylic resin varnish prepared within the scope of this application has a high solids content, and its viscosity is significantly lower than that of commercially available products, greatly improving its application performance in practical use. Even more superior is the excellent adhesion, high hardness, and acid and alkali resistance of the varnish prepared using it, achieving a significant improvement over the shortcomings of existing technologies.

[0098] The above-described embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A hydroxyl acrylic resin, characterized in that, The raw materials of the hydroxy acrylic resin, by mass percentage, consist of the following: 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, 20%-30% xylene, and 1%-15% butyl acetate; In the hydroxyl acrylic resin, the mass ratio of methyl-side-chain acrylic monomers to benzene-ring-containing hard monomers is 1:1.4-2.

8. The monomer conversion rate of the hydroxyl acrylic resin is 99%, the solid content is 66.6%-66.8%, and the viscosity of the resin is controlled at 1500-3000 mPa•s. The preparation method of the hydroxyl acrylic resin includes the following steps: 1) According to the formula, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and part of the initiator are drawn into a dropping container and stirred until a mixture is obtained; 2) Add a portion of xylene and the full amount of butyl acetate to the reactor as a base and heat it. Then, drop the mixture from the dropper into the reactor. After the addition is complete, continue copolymerization. 3) Add the remaining xylene and initiator, keep warm, then cool down and discharge the material.

2. The hydroxyl acrylic resin according to claim 1, characterized in that, The initiator is one of azobisisobutyronitrile, azobisisoheptane, benzoyl peroxide, cumene hydroperoxide, potassium persulfate, and ammonium persulfate.

3. The hydroxyl acrylic resin according to claim 2, characterized in that, The initiator is benzoyl peroxide.

4. The hydroxyl acrylic resin according to any one of claims 1 to 3, characterized in that, Step 1) includes: according to the ratio, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, and acrylic acid are drawn into a dropping tank, a portion of the initiator is weighed and added into the dropping tank, and stirring is started until it is dissolved evenly to obtain the mixture.

5. The hydroxyl acrylic resin according to claim 4, characterized in that, The amount of the initiator added is 80%.

6. The hydroxyl acrylic resin according to any one of claims 1 to 3, characterized in that, Step 2) includes: adding 80% of xylene and all of butyl acetate to the reaction vessel as a base and heating it; dripping the mixture from the dropper into the reaction vessel; and maintaining copolymerization for 1 hour after the addition is complete.

7. The hydroxyl acrylic resin according to claim 6, characterized in that, Add 80% of xylene and all of butyl acetate to the reactor as a base, and raise the temperature to 124±2℃ within 1.5 hours and maintain it for 10 minutes; At 124±2℃ and without reflux, the mixture in the dropping vessel is added dropwise into the reaction vessel over 2-2.5 hours, and copolymerization is maintained for 1 hour after the addition is complete.

8. The hydroxyl acrylic resin according to any one of claims 1 to 3, characterized in that, Step 3) includes: adding the remaining xylene and initiator mixture dropwise into the reactor at 124±2℃ over 5-10 minutes, maintaining copolymerization for 2 hours, and then cooling the reactor to 80℃ to discharge the hydroxyl acrylic resin.

9. A coating, wherein the raw material of the coating comprises any one of claims 1 to 8.

10. A coating formed from the coating of claim 9.

Citation Information

Patent Citations

  • High-solid low-viscosity hydroxy acrylic resin and preparation process thereof

    CN101921357A